(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the coverage of the armed struggle in Turkestan on the pages of the periodical press against the Soviet regime. The newspaper material revealing the nature and main factors of this movement and the reasons for it’s occurrence is analyzed.